2019
DOI: 10.1292/jvms.19-0254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of visceral fat mass in dogs by computed tomography

Abstract: In human medicine, computed tomography (CT) is the gold standard for visceral fat measurement. Research shows that the visceral fat area (VFA) of the umbilical slice is significantly correlated with the visceral fat volume (VFV). In veterinary medicine, however, few studies have evaluated visceral fat using CT. This study aimed to evaluate the visceral fat in dogs using CT images, and determine if the slice significantly correlated with VFV to simplify visceral fat measurements. This retrospective study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Our results showed that the total and visceral fat tend to accumulate at L3, whereas the subcutaneous fat tends to accumulate at L6 in all four breeds, findings that are consistent with the results of previous studies (Kim et al 2018;Nagao et al 2019). Therefore, it is thought that the fat distribution tendency remains the same regardless of the respective breed.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results showed that the total and visceral fat tend to accumulate at L3, whereas the subcutaneous fat tends to accumulate at L6 in all four breeds, findings that are consistent with the results of previous studies (Kim et al 2018;Nagao et al 2019). Therefore, it is thought that the fat distribution tendency remains the same regardless of the respective breed.…”
Section: Discussionsupporting
confidence: 93%
“…On the transverse CT images where spinous processes of L3 and L6 were the largest, the body area Figure 1 (BA), total fat area (TA), visceral fat area (VA), and subcutaneous fat area (SA) were measured based on previous studies (Ishioka et al 2005;Kim et al 2018;Nagao et al 2019) (Figure 1). Regions of interest (ROI) were drawn manually along the skin-air interface to assess the BA and TA.…”
Section: Imaging Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A 9-point scale BCS is usually used; the scoring is performed by visual observation and by palpating the dog [ 7 , 8 ]. Abdominal radiography and computed tomography (CT) can also be used to evaluate body fat distribution in humans and dogs [ 9 , 10 , 11 , 12 ]. Subcutaneous fat thickness (ST) can be measured using a lateral abdominal radiograph [ 10 ].…”
Section: Introductionmentioning
confidence: 99%